Numerical simulation of the heating process in a vacuum sintering electric furnace and structural optimization - Mao Li; Jishun Huang; Ting Hu; Benjun Cheng; Hesong Li (Scientific Reports)
Abstract A three-dimensional numerical model of the vacuum sintering furnace was established, combined with the custom program of temperature-voltage feedback regulation. Through simulationand experimental validation, the heating and holding stage as well as the thermal hysteresis phenomenon of the furnace were analyzed, a dimensionless quantity of hysteresis temperature difference was proposed and calculated, the distribution of the electric field and temperature uniformity of the furnace were discussed in detail, while the structural improvement approach was proposed based on simulation. The results show that: during the heating process, the maximum of thermal hysteresis temperature difference between the graphite cylinder and the heating tube is 0.4. The relative error between the simulation and measurement is within 4%, which verifies the accuracy of the model. By optimizing the structure of the heating tube and graphite base plate, the thermal hysteresis effect of the furnace can be effectively reduced, the surface load and the temperature difference between the surface of the heater can be significantly reduced, the temperature field and uniformity of the heating zone can be improved.